Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Di Kpp Pratama Batam Selatan - Sitanggang, Novia Christin; Efriyenti, Dian (Peneliti.net, 2023)
Taxpayer compliance is an important factor for the success of tax collection to meet their increasing tax obligations. This observation aims to analyze the factors that influence taxpayer compliance at KPP Pratama South Batam. This study used a descriptive and quantitative statistical approach with a sample of 100 respondents who were determined usingrandom sampling and using a questionnaire as a data collection instrument. From the analysis of the data obtained results that the implementatione-filling significant effect on taxpayer compliance with t count (3.875) > t table (1.984), knowledge of taxation has a significant effect on taxpayer compliance with t count (4.765) > t table (1.984) and service quality has an effect on taxpayer compliance with t count (2.551) > t table (1.984). Simultaneously application F test resultse-filling, Tax knowledge and service quality have a significant effect on taxpayer compliance with F count (83.268) > F table (2.698).